FEATURES OF EMOTIONAL INTELLIGENCE DEVELOPMENT OF PUBLIC SERVANTS - MATOKHNIUK, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the results of an empirical study of the level of emotional intelligence of public servants. The surveyed respondents are representatives of various positions and professions. Public managers, through regulation, management, financial management and strategy development, directly interact with colleagues, other people, which is reflected in the organizational and social development of society. Therefore, it is important to understand your emotions, understand the interlocutor, as well as the ability to manage your emotional sphere on the basis of decision-making. According to the obtained results, 64.56% of public servants have an average level of partial intelligence and 23.63% have a low level, and only 11.81% demonstrate a high level of manifestation of partial intelligence. None of the interviewed respondents demonstrated a high level of integrative emotional intelligence. Most of them namely 73.00% show average level and 27.00% show low level. It was revealed that the main reasons are low self-esteem and low motivation for self-development; low level of empathy and social responsibility; low adaptive abilities, etc. We assume that the reasons include the insufficient number of educational programs that would include the development of emotional intelligence, communication skills, and self-reflection; the general mood of society can also block the ability to recognize and express emotions. The general analysis of the study shows that the average level of emotional intelligence in the studied groups does not reach the expected standards, there are areas that need attention and development to achieve a higher level of emotional competence. It has been established that limited understanding, lack of skills and practice in using emotional intelligence at work can be a problem for successful management and leadership of public servants.
Keywords: emotional intelligence; personal block; leadership; public servant; professionalization